Tanggung Jawab dan Peranan Dewan Keamanan Perserikatan Bangsa-Bangsa dalam Memelihara Perdamaian dan Keamanan Internasional - Omba, Marthinus (UI Scholars Hub, 2008)
The main aim of the establishment of the United Nations is to maintain international peace and security based on the experiences of the First and Second World War, which being sorrow to mankind. The changing of the political map after Second World War and cold war; the making and trading modern weapons affect the United Nations responsibility. There was a critism, that the United Nations Security Council has not done yet its main tasks i.e. the maintenance of international peace and security. Thus, in this article, the writer wants to describe: the development of the stricture of the United Nations Security Council membership; the voting procedure; the functions and its authority; the role of the Security Council; the challenges and its responsibility.